Biomedical laboratory scientists’ collegiality in clinical laboratory work - Koskenvuori, Janika (fi=Turun yliopisto|en=University of Turku|, 2018)
Clinical laboratories are special health care environments, where the importance of collegiality can be argued through many environmental aspects. However, evidence-based knowledge on collegiality among biomedical laboratory scientists (BLSs) is lacking and therefore research in this field is needed. The objectives of the study were to draft an initial conceptual construct of collegiality of the BLSs, to achieve a well-formulated definition of the concept, and to find factors promoting and preventing collegiality of the BLSs. Explorative-descriptive study design was used. Twenty-three purposefully selected BLSs were recruited through two-staged sampling process in one hospital district. Participants were interviewed within five focus groups in May and June 2016. Data were analysed using inductive content analysis method. BLSs’ collegiality emerged through ethical and actional manifestations. From the ethical perspective, collegiality manifested as a communal professional value. Collegiality was based on common profession and goals, and it was a factor guiding actions of the peers, a desired and sought-after state, and shaped by individual and communal factors. Collegiality was formed by nine ethical-humane virtues which were peers’ mutual appreciation, compassion, confidence and trust, courage, equality, loyalty, respect, responsibility and tolerance. From the actional perspective, collegiality was realized through peers’ collaboration and communication. Collaboration was manifested and realized through co-operation, fair and flexible division of work, peer helping and mutual learning. Communication was realized through consensus decision-making, giving and receiving feedback, mutual problem solving, open discussion and information sharing, and peer consulting. Promoting factors of collegiality were sufficient leadership, open communication climate, proper social interaction, active and well-being individuals, and enhancement of employees’ control over work. Preventing factors included poor leadership, uncontrollable overloading factors at work, and dysfunctional social interaction within work group. This study is one of the first studies investigating collegiality or any other ethical aspects among BLSs, and thus, it provides useful knowledge and implications for BLSs, organizations, education and research. Future research should focus on development of an instrument to measure collegiality and on development of interventions to promote collegiality. Furthermore, to find work-related factors associated with collegiality and to study leaders’ ability to promote collegiality are recommended. In addition, due to migration of healthcare workers, international studies regarding BLSs’ collegiality are recommended.